Pelatihan Pemanfaatan Tanaman Pekarangan Berbasis Teknologi Informasi Sebagai Pemberdayaan Masyarakat Terdampak Bencana COVID-19 - Rahmat Widia Sembiring; Benny B. Nasution; Rina Walmiaty Mardi (LPPM STIKOM Tunas Bangsa, 2020)
Tanjung Baru Village is located in Tanjung Morawa District, North Sumatra Province, 15 KM from Medan City. Some of the village clan work as buurt for the company. As a result of the impact of the Covid-19 pandemic, some residents experienced layoffs, so that the residents' economy was disrupted. To help the villagers, it is necessary to train in the skills of planting yard plants with a hydroponic system that produces products of economic value.